Contribution of TMS and rTMS in the Understanding of the Pathophysiology and in the Treatment of Dystonia - Lozeron, Pierre; Poujois, Aurélia; Richard, Alexandra; Masmoudi, Sana; Meppiel, Elodie; Woimant, France; Kubis, Nathalie (Frontiers in Neural Circuits, 2016)
Dystonias represent a heterogeneous group of movement disorders responsible for sustained muscle contraction, abnormal postures and muscle twists. It can affect focal or segmental body parts or be generalized. Primary dystonia is the most common form of dystonia but it can also be secondary to metabolic or structural dysfunction, the consequence of a drug’s side-effect or of genetic origin. The pathophysiology is still not elucidated. Based on lesion studies, dystonia has been regarded as a pure motor dysfunction of the basal ganglia loop. However, basal ganglia lesions do not consistently produce dystonia and lesions outside basal ganglia can lead to dystonia; mild sensory abnormalities have been reported in the dystonic limb and imaging studies have shown involvement of multiple other brain regions including the cerebellum and the cerebral motor, premotor and sensorimotor cortices. Transcranial magnetic stimulation (TMS) is a non-invasive technique of brain stimulation with a magnetic field applied over the cortex allowing investigation of cortical excitability. Hyperexcitability of contralateral motor cortex has been suggested to be the trigger of focal dystonia. High or low frequency repetitive TMS (rTMS) can induce excitatory or inhibitory lasting effects beyond the time of stimulation and protocols have been developed having either a positive or a negative effect on cortical excitability and associated with prevention of cell death, γ-aminobutyric acid (GABA) interneurons mediated inhibition and brain-derived neurotrophic factor (BDNF) modulation. rTMS studies as a therapeutic strategy of dystonia have been conducted to modulate the cerebral areas involved in the disease. Especially, when applied on the contralateral (pre)-motor cortex or supplementary motor area of brains of small cohorts of dystonic patients, rTMS has shown a beneficial transient clinical effect in association with restrained motor cortex excitability. TMS is currently a valuable tool to improve our understanding of the pathophysiology of dystonia but large controlled studies using sham stimulation are still necessary to delineate the place of rTMS in the therapeutic strategy of dystonia. In this review, we will focus successively on the use of TMS as a tool to better understand pathophysiology, and the use of rTMS as a therapeutic strategy.